Analysis of Factors Influencing The Shift from Rice to Maize In Lembantongoa Village, Sigi Regency, Indonesia - Umam, Sirajul; Sading, Yunus; Musdayanti, M.; Yunus, Rita; Tallesang, Mukhtar (Golden Ratio of Data in Summary, 2025)
This study analyzes the factors that drive farmers to shift from cultivating lowland rice to corn in Lembantongoa Village, Palolo District, Sigi Regency. Using a descriptive qualitative method, data were collected through observation, interviews, and questionnaires, with proportional random sampling. Analysis was conducted using frequency distribution tables. Findings reveal that the shift was mainly due to declining rice productivity, which reduced farmer income. Corn was chosen as an alternative because of its shorter harvesting period and higher economic value. Data from 2015 to 2022 show a 4.6% decrease in rice planting area and an 11.2% increase in corn. These economic and environmental factors have influenced the village farmers' transition.